Method for preparing iron cobaltate diaphragm based on waste lithium iron phosphate positive electrode material

By recycling iron phosphate from waste lithium iron phosphate batteries and preparing iron cobalt acid separator materials, the problems of unused waste lithium ion battery resources and degraded lithium sulfur battery performance are solved, and resource recycling and battery performance are improved.

CN119905705APending Publication Date: 2025-04-29UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510047815.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The valuable metal resources in waste lithium-ion batteries have not been effectively recycled and reused, resulting in waste of resources and environmental pollution. At the same time, lithium-sulfur batteries face capacity attenuation and degradation of cycling performance caused by polysulfide shuttle effect in practical applications.

Method used

Lithium iron phosphate is recovered from the positive electrode material of waste lithium iron phosphate battery by using the organic acid method, converted to iron phosphate, and the iron cobalt acid separator material is prepared using this material to improve the circulation performance and stability of lithium sulfur batteries.

Benefits of technology

It realizes the effective recycling of waste battery materials, reduces environmental pollution, improves the sustainability of battery materials, and provides excellent separator materials for lithium-sulfur batteries, improving its energy density and circulation stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905705A_ABST
    Figure CN119905705A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery material recovery and reutilization, and particularly relates to a method for preparing an iron cobaltate diaphragm based on a waste lithium iron phosphate positive electrode material and application of the iron cobaltate diaphragm. Then leaching, filtering and washing to obtain a solid product lithium iron phosphate, and aging, centrifugally washing and drying the lithium iron phosphate, and heating in a nitrogen environment to obtain an iron cobaltate product; and finally, adding conductive carbon black and polyvinylidene fluoride into iron cobaltate to prepare the iron cobaltate diaphragm. According to the method, the lithium iron phosphate LiFePO4 is recycled from the positive electrode material of the waste lithium iron phosphate battery by adopting an organic acid method, and is converted into the iron phosphate FePO4 to prepare the iron cobaltate diaphragm material, so that the effective recycling of resources is realized, the environmental pollution is reduced, and the sustainability of the battery material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery material recovery and reuse, and specifically relates to a method for preparing an iron cobaltate diaphragm based on waste lithium iron phosphate positive electrode materials and application thereof. Background Art

[0002] With the increasing global demand for renewable energy and clean energy, the new energy vehicle market is showing a rapid growth trend. The widespread use of electric vehicles and portable electronic devices has led to a sharp increase in the demand for lithium-ion batteries. However, the problem of waste battery disposal has become increasingly prominent. Waste lithium-ion batteries contain a large amount of valuable metals, such as lithium and iron. If they are directly discarded, it will not only cause a waste of resources, but also cause serious pollution to the environment. Therefore, it is particularly important to develop efficient and environmentally friendly waste battery material recycling and reuse technologies.

[0003] In recent years, the recycling technology of waste lithium-ion batteries has received widespread attention and has made some progress. In 2010, pyrometallurgical technology began to be widely used in the field of waste lithium-ion battery recycling, but this technology has high energy consumption and is prone to secondary pollution. After 2015, hydrometallurgical technology, especially inorganic acid leaching, gradually became the mainstream recycling technology. However, these strong acids are corrosive and accompanied by safety hazards during transportation, storage and use. Since 2020, organic acid leaching has gradually been favored by researchers due to its lower corrosiveness and higher safety, and has become a more environmentally friendly recycling method. In addition, lithium-sulfur batteries are also considered to be one of the candidates for the next generation of energy storage systems because of their high theoretical energy density (about 2600Wh / kg) and low cost. However, lithium-sulfur batteries face many challenges in practical applications, and the polysulfide shuttle effect is one of them. This effect causes the battery capacity to decay rapidly and the cycle performance to decline. In order to suppress the polysulfide shuttle effect, it is necessary to use efficient diaphragm materials to improve the cycle performance and stability of the battery.

[0004] As early as 2012, researchers began to explore the potential of cobalt iron oxide (CoFe 2 O 4 ) as a lithium-sulfur battery separator material. Subsequently, a number of studies have shown that iron cobalt oxide can not only effectively block the shuttling of polysulfides, but also provide good conductivity and mechanical strength. In 2018, related studies further confirmed the potential of iron cobalt oxide in improving the performance of lithium-sulfur batteries, making iron cobalt oxide an important candidate for lithium-sulfur battery separator materials.

[0005] Therefore, studying a method for preparing iron cobalt oxide diaphragm materials for lithium-sulfur batteries based on the recycling process of waste lithium iron phosphate positive electrode materials can not only solve the problem of handling waste battery materials, but also provide new diaphragm materials for high-performance lithium-sulfur batteries. Summary of the invention

[0006] The purpose of the present invention is to provide a method and application of preparing an iron cobalt oxide diaphragm based on waste lithium iron phosphate positive electrode materials, and to recover lithium iron phosphate LiFePO from waste lithium iron phosphate battery positive electrode materials by an organic acid method. 4 , and converted into iron phosphate FePO 4 To prepare iron cobaltate diaphragm materials, it realizes the effective recycling of resources, reduces environmental pollution and improves the sustainability of battery materials.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] The method for preparing an iron cobaltate diaphragm based on waste lithium iron phosphate positive electrode material comprises the following steps:

[0009] Step 1: Classify the waste lithium iron phosphate battery materials to obtain lithium iron phosphate positive electrode sheets;

[0010] Step 2: The lithium iron phosphate positive electrode sheet, the citric acid solution with a concentration of 1.0-1.5 mol / L, and the ascorbic acid solution with a solution ratio of 1:1 are mixed and added into a container, and the solid product FePO is obtained by leaching reaction, filtering, and washing. 4 ;

[0011] Step 3: CoCl 2 ·6H2O and trisodium citrate dihydrate were dissolved in deionized water to prepare solution A. The FePO obtained in step 2 was added 4 Dissolve in deionized water to prepare solution B;

[0012] Step 4, slowly pouring solution B into the stirring solution A, the volume ratio of solution A to solution B is 4:5, and after mixing evenly, continue stirring for 8 to 15 minutes to obtain a mixed solution;

[0013] Step 5, aging, centrifugation washing, and drying the mixed solution in sequence to obtain a Co-PBA product;

[0014] Step 6: heat-treating the Co-PBA product obtained in step 5. Specifically, the Co-PBA product obtained in step 5 is placed in a tube furnace, heated to 400°C in a nitrogen environment and maintained, and then cooled to room temperature to obtain cobalt iron (CoFe 2 O 4 );

[0015] Step 7: Cobalt iron oxide (CoFe 2 O 4 ), conductive carbon black Super P, and polyvinylidene fluoride (PVDF) are uniformly ground in a mass ratio of 8:1:1, and then NMP is added in a volume ratio of 1:1 to the ground material for further uniform grinding, and then coated on a PP separator and dried at a temperature of 50-70°C to obtain a cobalt iron separator for a lithium-sulfur battery separator modification material.

[0016] Furthermore, the leaching reaction temperature in step 2 is 80°C.

[0017] Further, in step 3, CoCl 2 ·6H2O and trisodium citrate dihydrate are dissolved in 60 mL of deionized water at a molar ratio of 1:1 to 1:2.

[0018] Furthermore, the aging method in step 5 is: placing the mixed solution in an oven at 40-60°C for aging for 36 hours; the centrifugal washing method is: using ethanol and deionized water to repeatedly centrifuge and wash 4 times; the drying method is: drying in an oven at 60°C for 12-24 hours.

[0019] Furthermore, the heat treatment conditions in step 6 are as follows: Co-PBA is heated to 400° C. at a heating rate of 2-5° C. / min in a nitrogen environment and maintained for 2-4 hours.

[0020] The method for preparing the cobalt iron oxide diaphragm based on waste lithium iron phosphate positive electrode materials adopts a mixed solution of citric acid and ascorbic acid for leaching treatment, thereby avoiding the corrosiveness and potential safety hazards caused by the traditional inorganic strong acid method, and significantly improving the safety and environmental protection of the operation. Through effective chemical treatment steps, the lithium element in the waste lithium iron phosphate battery positive electrode material is effectively extracted, and the lithium iron phosphate (LiFePO 4 ) is converted into iron phosphate (FePO 4 ). The recovered FePO 4It is further used to prepare cobalt iron oxide diaphragm materials, thereby realizing the recycling of waste battery materials and reducing resource waste. At the same time, during the preparation of experimental materials, heat treatment under a nitrogen environment helps to maintain the chemical composition and crystal structure of the material stable, avoiding the impact of oxygen in the air on the surface of the material. This makes the prepared cobalt iron oxide have excellent electrochemical properties, which has a positive impact on the energy density and cycle stability of energy storage devices such as lithium-ion batteries. At the same time, the chemical stability and thermal stability of the material are also enhanced due to nitrogen protection. In addition, the morphology of cobalt iron oxide can be controlled by regulating the synthesis conditions, and uniformly dispersed, small-sized and concentrated nanoparticles can be obtained, which may appear cubic. Small particle size and high specific surface area are conducive to increasing the number of active sites in the material, thereby improving its catalytic activity or performance as an electrode material. These special structures can further optimize the functional properties of the material.

[0021] The prepared iron cobaltate (CoFe 2 O 4 ) The diaphragm material exhibits excellent electrochemical properties, which meets the application requirements of high-performance lithium-sulfur batteries. Specifically, its initial discharge capacity is relatively high, reaching 1200mAh / g under 1C current charge and discharge conditions; under 2C current charge and discharge conditions, the discharge capacity remains above 970mAh / g after 100 cycles; after 100 charge and discharge cycles at 0.5C current density, the capacity retention rate is over 90%, and the charge and discharge efficiency of all test processes is over 97%, with good cycle stability. The battery was tested at rates of 0.5C, 1C, 2C, 3C, 2C, and 1C, with 10 cycles at each rate, and finally a capacity recovery rate of up to 92% was achieved at 1C. With these performance indicators, this material is undoubtedly an ideal choice for lithium-sulfur battery diaphragms.

[0022] The entire preparation process is simple and easy, including key steps such as leaching, separation, synthesis and heat treatment. These steps are easy to operate and suitable for large-scale production scenarios, which helps to reduce production costs and improve production efficiency. In addition, the prepared iron cobalt oxide diaphragm material not only solves the problem of handling waste battery materials, but also provides high-quality diaphragm materials for lithium-sulfur batteries, significantly improving the overall performance and service life of the battery. The material is also expected to expand to the application fields of other types of energy storage devices, showing broad application prospects.

[0023] In summary, the present invention provides a simple, efficient and environmentally friendly solution for the recovery and reuse of waste lithium iron phosphate battery positive electrode materials, which not only realizes the effective recycling of resources, but also provides high-quality diaphragm materials for high-performance lithium-sulfur batteries, thereby promoting the development of clean energy technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Example 1 Process flow chart for recycling and preparing lithium-sulfur battery iron cobalt oxide diaphragm material;

[0025] Figure 2 This is a schematic diagram of the structure of the iron cobaltate material recovered and prepared in Example 1;

[0026] Figure 3 This is a rate performance diagram of the lithium-sulfur battery recovered and prepared in Example 1;

[0027] Figure 4 Cycling performance diagram of a lithium-sulfur battery prepared for recycling. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0029] Example 1

[0030] like Figure 1 As shown, the method for preparing an iron cobaltate separator based on waste lithium iron phosphate positive electrode material provided in this embodiment includes the following steps:

[0031] Step 1: Classify the waste lithium iron phosphate battery materials to obtain lithium iron phosphate positive electrode sheets.

[0032] Step 2: Mix the lithium iron phosphate positive electrode sheet, a citric acid solution with a concentration of 1.0 mol / L, and an ascorbic acid solution with a concentration of 0.1 mol / L in a solution ratio of 1:1 and add them to a container; place the container in an 80°C water bath for leaching reaction for 60 minutes; after the reaction is completed, separate the solid product FePO by filtering and washing. 4 .

[0033] Step 3: Weigh 3 mmol of CoCl 2 ·6H2O and 3mmol of trisodium citrate dihydrate were dissolved in 60mL of deionized water, labeled as solution A; the FePO obtained in step 2 was 4 Dissolve in 75 mL of deionized water to prepare solution B.

[0034] Step 4: Slowly pour solution B into the stirring solution A, mix well and continue stirring for 10 minutes to obtain a mixed solution.

[0035] Step 5: Place the mixed solution in an oven at 40°C and age it for 36 hours. After the reaction is completed, use ethanol and deionized water to repeatedly centrifuge and wash it 4 times, and dry it in an oven at 60°C for 12 hours to obtain Co-PBA.

[0036] Step 6: Place the dried Co-PBA product in a tube furnace, heat it to 400°C at a heating rate of 2°C / min in a nitrogen environment and maintain it for 2 hours; after cooling to room temperature, cobalt iron (CoFe 2 O 4 ).

[0037] Step 7: Grind the obtained iron cobaltate, Super P, and PVDF uniformly at a mass ratio of 8:1:1, add an appropriate amount of NMP and grind them uniformly again, and then quickly apply them on the PP diaphragm, and place the coated iron cobaltate-modified diaphragm in a 60°C oven for 24 hours.

[0038] Step 8: Use the iron cobalt oxide diaphragm obtained in step 7 as a diaphragm modification material for a lithium-sulfur battery to assemble the lithium-sulfur battery.

[0039] Example 2

[0040] Step 1: Classify the waste lithium iron phosphate battery materials to obtain lithium iron phosphate positive electrode sheets.

[0041] Step 2: Mix the lithium iron phosphate positive electrode sheet, a citric acid solution with a concentration of 1.5 mol / L, and an ascorbic acid solution with a concentration of 0.1 mol / L in a solution ratio of 1:1 and add them to a three-necked flask; place it in an 80°C water bath for leaching reaction for 60 minutes; after the reaction is completed, separate the solid product FePO by filtering and washing. 4 .

[0042] Step 3: Weigh 3 mmol of CoCl 2 ·6H2O and 3mmol of trisodium citrate dihydrate were dissolved in 60mL of deionized water, labeled as solution A; the FePO obtained in step 2 was 4 Dissolve in 75 mL of deionized water to prepare solution B.

[0043] Step 4: Slowly pour solution B into the stirring solution A, mix well and continue stirring for 10 minutes to obtain a mixed solution.

[0044] Step 5: Place the mixed solution in an oven at 40°C and age it for 36 hours. After the reaction is completed, use ethanol and deionized water to repeatedly centrifuge and wash it 4 times, and dry it in an oven at 60°C for 12 hours to obtain Co-PBA.

[0045] Step 6: Place the dried Co-PBA product in a tube furnace, heat it to 400°C at a heating rate of 2°C / min in a nitrogen environment and maintain it for 2 hours; after cooling to room temperature, cobalt iron (CoFe 2 O 4 ).

[0046] Step 7: Grind the obtained iron cobaltate, Super P, and PVDF uniformly at a mass ratio of 8:1:1, add an appropriate amount of NMP and grind them uniformly again, and then quickly apply them on the PP diaphragm, and place the coated iron cobaltate-modified diaphragm in a 60°C oven for 24 hours.

[0047] Step 8: Use the iron cobalt oxide diaphragm obtained in step 7 as a diaphragm modification material for a lithium-sulfur battery to assemble the lithium-sulfur battery.

[0048] Example 3

[0049] Step 1: Classify the waste lithium iron phosphate battery materials to obtain lithium iron phosphate positive electrode sheets.

[0050] Step 2: Mix the lithium iron phosphate positive electrode sheet, 1.5 mol / L citric acid solution, and 0.3 mol / L ascorbic acid solution in a ratio of 1:1 and add them to a container; put the three-necked flask into a three-necked flask; place the three-necked flask in an 80°C water bath for leaching reaction for 60 minutes; after the reaction is completed, separate the solid product FePO by filtering and washing. 4 .

[0051] Step 3: Weigh 3 mmol of CoCl 2 ·6H2O and 3mmol of trisodium citrate dihydrate were dissolved in 60mL of deionized water, labeled as solution A; the FePO obtained in step 2 was 4 Dissolve in 75 mL of deionized water to prepare solution B.

[0052] Step 4: Slowly pour solution B into the stirring solution A, mix well and continue stirring for 10 minutes to obtain a mixed solution.

[0053] Step 5: Place the mixed solution in an oven at 40°C and age it for 36 hours. After the reaction is completed, use ethanol and deionized water to repeatedly centrifuge and wash it 4 times, and dry it in an oven at 60°C for 12 hours to obtain Co-PBA.

[0054] Step 6: Place the dried Co-PBA product in a tube furnace, heat it to 400°C at a heating rate of 2°C / min in a nitrogen environment and maintain it for 2 hours; after cooling to room temperature, cobalt iron (CoFe 2 O 4 ).

[0055] Step 7: Grind the obtained iron cobaltate, Super P, and PVDF uniformly at a mass ratio of 8:1:1, add an appropriate amount of NMP and grind them uniformly again, and then quickly apply them on the PP diaphragm, and place the coated iron cobaltate-modified diaphragm in a 60°C oven for 24 hours.

[0056] Step 8: Use the iron cobalt oxide diaphragm obtained in step 7 as a diaphragm modification material for a lithium-sulfur battery to assemble the lithium-sulfur battery.

[0057] Example 4

[0058] Step 1: Classify the waste lithium iron phosphate battery materials to obtain lithium iron phosphate positive electrode sheets.

[0059] Step 2: Mix the lithium iron phosphate positive electrode sheet, a citric acid solution with a concentration of 1.5 mol / L, and an ascorbic acid solution with a concentration of 0.3 mol / L in a solution ratio of 1:1 and add them to a three-necked flask; place the three-necked flask in an 80°C water bath for leaching reaction for 60 minutes; after the reaction is completed, separate the solid product FePO by filtering and washing. 4 .

[0060] Step 3: Weigh 2 mmol of CoCl 2 ·6H2O and 4mmol of trisodium citrate dihydrate were dissolved in 60mL of deionized water, labeled as solution A; the FePO obtained in step 2 was 4 Dissolve in 75 mL of deionized water to prepare solution B.

[0061] Step 4: Slowly pour solution B into the stirring solution A, mix well and continue stirring for 10 minutes to obtain a mixed solution.

[0062] Step 5: Place the mixed solution in an oven at 40°C and age it for 36 hours. After the reaction is completed, use ethanol and deionized water to repeatedly centrifuge and wash it 4 times, and dry it in an oven at 60°C for 12 hours to obtain Co-PBA.

[0063] Step 6: Place the dried Co-PBA product in a tube furnace, heat it to 400°C at a heating rate of 2°C / min in a nitrogen environment and maintain it for 2 hours; after cooling to room temperature, cobalt iron (CoFe 2 O 4 ).

[0064] Step 7: Grind the obtained iron cobaltate, Super P, and PVDF uniformly at a mass ratio of 8:1:1, add an appropriate amount of NMP and grind them uniformly again, and then quickly apply them on the PP diaphragm, and place the coated iron cobaltate-modified diaphragm in a 60°C oven for 24 hours.

[0065] Step 8: Use the iron cobalt oxide diaphragm obtained in step 7 as a diaphragm modification material for a lithium-sulfur battery to assemble the lithium-sulfur battery.

[0066] Example 5

[0067] Step 1: Classify the waste lithium iron phosphate battery materials to obtain lithium iron phosphate positive electrode sheets.

[0068] Step 2: Mix the lithium iron phosphate positive electrode sheet, a citric acid solution with a concentration of 1.5 mol / L, and an ascorbic acid solution with a concentration of 0.3 mol / L in a solution ratio of 1:1 and add them to a three-necked flask; place the three-necked flask in an 80°C water bath for leaching reaction for 60 minutes; after the reaction is completed, separate the solid product FePO by filtering and washing. 4 .

[0069] Step 3: Weigh 3 mmol of CoCl 2 ·6H2O and 3mmol of trisodium citrate dihydrate were dissolved in 60mL of deionized water, labeled as solution A; the FePO obtained in step 2 was 4 Dissolve in 75 mL of deionized water to prepare solution B.

[0070] Step 4: Slowly pour solution B into the stirring solution A, mix well and continue stirring for 10 minutes to obtain a mixed solution.

[0071] Step 5: Place the mixed solution in an oven at 40°C and age it for 36 hours. After the reaction is completed, use ethanol and deionized water to repeatedly centrifuge and wash it 4 times, and dry it in an oven at 60°C for 12 hours to obtain Co-PBA.

[0072] Step 6: Place the dried Co-PBA product in a tube furnace, heat it to 400°C at a heating rate of 2°C / min in a nitrogen environment and maintain it for 2 hours; after cooling to room temperature, cobalt iron (CoFe 2 O 4 ).

[0073] Step 7: Grind the obtained iron cobaltate, Super P, and PVDF uniformly at a mass ratio of 8:1:1, add an appropriate amount of NMP and grind them uniformly again, and then quickly apply them on the PP diaphragm, and place the coated iron cobaltate-modified diaphragm in a 60°C oven for 24 hours.

[0074] Step 8: Use the iron cobalt oxide diaphragm obtained in step 7 as a diaphragm modification material for a lithium-sulfur battery to assemble the lithium-sulfur battery.

[0075] Example 6

[0076] Step 1: Classify the waste lithium iron phosphate battery materials to obtain lithium iron phosphate positive electrode sheets.

[0077] Step 2: Mix the lithium iron phosphate positive electrode sheet, a citric acid solution with a concentration of 1.5 mol / L, and an ascorbic acid solution with a concentration of 0.3 mol / L in a solution ratio of 1:1 and add them to a three-necked flask; place the three-necked flask in an 80°C water bath for leaching reaction for 60 minutes; after the reaction is completed, separate the solid product FePO by filtering and washing. 4 .

[0078] Step 3: Weigh 3 mmol of CoCl 2 ·6H2O and 3mmol of trisodium citrate dihydrate were dissolved in 60mL of deionized water, labeled as solution A; the FePO obtained in step 2 was 4 Dissolve in 75 mL of deionized water to prepare solution B.

[0079] Step 4: Slowly pour solution B into the stirring solution A, mix well and continue stirring for 10 minutes to obtain a mixed solution.

[0080] Step 5: Place the mixed solution in an oven at 40°C and age it for 36 hours. After the reaction is completed, use ethanol and deionized water to repeatedly centrifuge and wash it 4 times, and dry it in an oven at 60°C for 12 hours to obtain Co-PBA.

[0081] Step 6: Place the dried Co-PBA product in a tube furnace, heat to 400°C at a heating rate of 5°C / min in a nitrogen environment and maintain for 2 hours; after cooling to room temperature, cobalt iron (CoFe 2 O 4 ).

[0082] Step 7: Grind the obtained iron cobaltate, Super P, and PVDF uniformly at a mass ratio of 8:1:1, add an appropriate amount of NMP and grind them uniformly again, and then quickly apply them on the PP diaphragm, and place the coated iron cobaltate-modified diaphragm in a 60°C oven for 24 hours.

[0083] Step 8: Use the iron cobalt oxide diaphragm obtained in step 7 as a diaphragm modification material for a lithium-sulfur battery to assemble the lithium-sulfur battery.

[0084] Example 7

[0085] Step 1: Classify the waste lithium iron phosphate battery materials to obtain lithium iron phosphate positive electrode sheets.

[0086] Step 2: Mix the lithium iron phosphate positive electrode sheet, a citric acid solution with a concentration of 1.5 mol / L, and an ascorbic acid solution with a concentration of 0.3 mol / L in a solution ratio of 1:1 and add them to a three-necked flask; place the three-necked flask in an 80°C water bath for leaching reaction, wherein the solid-liquid ratio during the leaching reaction is 1:20 and the reaction time is 60 minutes; after the reaction is completed, separate the solid product FePO by filtering and washing. 4 .

[0087] Step 3: Weigh 3 mmol of CoCl 2 ·6H2O and 3mmol of trisodium citrate dihydrate were dissolved in 60mL of deionized water, labeled as solution A; the FePO obtained in step 2 was 4 Dissolve in 75 mL of deionized water to prepare solution B.

[0088] Step 4: Slowly pour solution B into the stirring solution A, mix well and continue stirring for 10 minutes to obtain a mixed solution.

[0089] Step 5: Place the mixed solution in an oven at 40°C and age it for 36 hours. After the reaction is completed, use ethanol and deionized water to repeatedly centrifuge and wash it 4 times, and dry it in an oven at 60°C for 12 hours to obtain Co-PBA.

[0090] Step 6: Place the dried Co-PBA product in a tube furnace, heat to 400°C at a heating rate of 5°C / min in a nitrogen environment and maintain for 2 hours; after cooling to room temperature, cobalt iron (CoFe 2 O 4 ).

[0091] Step 7: Grind the obtained iron cobaltate, Super P, and PVDF uniformly at a mass ratio of 8:1:1, add an appropriate amount of NMP and grind them uniformly again, and then quickly apply them on the PP diaphragm, and place the coated iron cobaltate-modified diaphragm in a 60°C oven for 24 hours.

[0092] Step 8: Use the iron cobalt oxide diaphragm obtained in step 7 as a diaphragm modification material for a lithium-sulfur battery to assemble the lithium-sulfur battery.

[0093] Figure 2 This is a schematic diagram of the structure of the iron cobaltate material recovered and prepared in Example 1, see Figure 2It can be seen that Co-PBA itself has clear cubic morphological characteristics, and these characteristics have a significant impact on the morphology of the final product during the heat treatment process. The pyrolysis process carried out under nitrogen protection makes the cobalt iron converted from Co-PBA inherit its cubic phase crystal structure, presenting an approximate cubic or morphology. Since the starting material is composed of nanoscale building blocks, the cobalt iron after heat treatment also remains at the nanoscale. In addition, the porosity and large specific surface area characteristics of Co-PBA are retained during the sintering process under a nitrogen atmosphere, so that the final cobalt iron material has a large specific surface area, which is very beneficial for applications such as catalysis and adsorption. Material synthesis in a nitrogen environment can effectively avoid excessive oxidation or other side reactions caused by an oxidizing atmosphere, and secondly, promote the occurrence of nitrogen doping to further adjust the physical and chemical properties of the material, such as improving conductivity or changing magnetic properties.

[0094] Therefore, the iron cobalt oxide material prepared by this nitrogen environment synthesis method shows the characteristics of regular morphology, controllable size, good dispersibility, and is likely to be nitrogen-doped. These characteristics are crucial for the actual performance of iron cobalt oxide materials in many application fields.

[0095] Figure 3 This is the rate performance diagram of the lithium-sulfur battery prepared in Example 1, see Figure 3 It can be seen that in the rate test, the prepared cobalt iron oxide diaphragm lithium-sulfur battery achieved high specific capacities of 1305, 1229, 1149, and 910 mAh / g at fast charging rates of 0.5C, 1C, 2C, and 3C, respectively, and also reached 1145 mAh / g when it was subsequently restored to 1C, i.e. a high recovery rate of 93%, all of which indicate that the prepared cobalt iron oxide diaphragm lithium-sulfur battery has excellent performance and stability.

[0096] Figure 4 The cycle performance diagram of the lithium-sulfur battery prepared for implementation 1 shows that under the current charge and discharge conditions of 2C, the discharge capacity is still maintained above 970mAh / g after 100 cycles; under the current density of 0.5C, the initial discharge capacity is as high as 1308mAh / g. After 100 charge and discharge cycles, the capacity retention rate is more than 90%, and the charge and discharge efficiency of all test processes is above 97%.

Claims

1. A method for preparing an iron cobaltate diaphragm based on waste lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: Step 1: Classify the waste lithium iron phosphate battery materials to obtain lithium iron phosphate positive electrode sheets; Step 2, a lithium iron phosphate positive electrode sheet, a citric acid solution with a concentration of 1.0-1.5 mol / L, and an ascorbic acid solution with a solution ratio of 1:1 are mixed and added into a container, and a solid product FePO4 is obtained by leaching reaction, filtering, and washing; Step 3, dissolving CoCl2·6H2O and trisodium citrate dihydrate in deionized water to prepare solution A, and dissolving FePO4 obtained in step 2 in deionized water to prepare solution B; Step 4, slowly pouring solution B into the stirring solution A, the volume ratio of solution A to solution B is 4:5, and after mixing evenly, continue stirring for 8 to 15 minutes to obtain a mixed solution; Step 5, aging, centrifugation washing, and drying the mixed solution in sequence to obtain a Co-PBA product; Step 6, heat treating the Co-PBA product obtained in step 5, specifically: placing the Co-PBA product obtained in step 5 in a tube furnace, heating to 400° C. and maintaining in a nitrogen environment, and then cooling to room temperature to obtain cobalt iron oxide (CoFe2O4); Step 7, cobalt iron (CoFe2O4), conductive carbon black Super P, and polyvinylidene fluoride (PVDF) are uniformly ground in a mass ratio of 8:1:1, and then NMP is added in a volume ratio of 1:1 to the ground material for further uniform grinding, and then coated on a PP diaphragm and dried at a temperature of 50 to 70°C to obtain a cobalt iron diaphragm for a lithium-sulfur battery diaphragm modification material.

2. The method according to claim 1, characterized in that The leaching reaction temperature in step 2 is 80°C.

3. The method according to claim 1, characterized in that In step 3, CoCl2·6H2O and trisodium citrate dihydrate are dissolved in 60 mL of deionized water at a molar ratio of 1:1 to 1:

2.

4. The method according to claim 1, characterized in that: The aging method in step 5 is: placing the mixed solution in an oven at 40-60° C. for aging for 36 hours; the centrifugal washing method is: using ethanol and deionized water to repeatedly centrifuge and wash 4 times; the drying method is: drying in an oven at 60° C. for 12-24 hours.

5. The method according to claim 1, characterized in that The heat treatment conditions in step 6 are as follows: Co-PBA is heated to 400° C. at a heating rate of 2-5° C. / min in a nitrogen environment and maintained for 2-4 hours.

6. Use of the cobalt-iron hollow composite diaphragm prepared by the method according to claims 1 to 5 in lithium-sulfur batteries.